2021
DOI: 10.1016/j.breast.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of postmastectomy hypofractionated radiation therapy vs conventional fractionated radiation therapy for high-risk breast cancer

Abstract: postmastectomy hypofractionated radiation therapy vs conventional fractionated radiation therapy for high-risk breast cancer, The Breast,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…These findings are like other studies which demonstrate a QALY gain ranging from 0.19 to 0.76. 10 , 12 , 13 , 39 In terms of ICER, our findings are consistent with other studies in different settings. Wan et al reports that PMRT for patients with 1–3 node involvement is cost-effective in China, however, uncertainty of PMRT being cost-effective are relatively greater for patients with pN4+.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are like other studies which demonstrate a QALY gain ranging from 0.19 to 0.76. 10 , 12 , 13 , 39 In terms of ICER, our findings are consistent with other studies in different settings. Wan et al reports that PMRT for patients with 1–3 node involvement is cost-effective in China, however, uncertainty of PMRT being cost-effective are relatively greater for patients with pN4+.…”
Section: Discussionsupporting
confidence: 92%
“…A study from the USA reported that HFRT could save the US healthcare system millions of dollars in healthcare costs if it follows evidence-based practice guidelines and if expert advice is chosen appropriately (63). In addition, despite population differences, recent studies have demonstrated for the first time that post-mastectomy HFRT is often more cost-effective than CFRT for women at high risk of breast cancer in China, France, and the United States (64).…”
Section: Discussionmentioning
confidence: 99%
“…31 A study on the cost effectiveness of hypofractionated compared with conventionally fractionated postmastectomy breast radiation in China found that it was associated with an 11% cost reduction and was determined to be cost-effective. 54 Another study from China reported that neoadjuvant 10-fraction hypofractionated radiation for esophageal cancer resulted in a 41% reduction in radiotherapy costs over a 20-fraction moderately hypofractionated regimen. 53 Reducing the treatment costs patients incur is equally important to reducing the costs for the overall health care system.…”
Section: Reduced Costsmentioning
confidence: 99%